Vaccination as a way forward? A case study on how a poultry vaccination intervention influences poultry keeping in Kenya - Lindahl, Johanna F.; Wyatt, Amanda; Young, J.; Young, M.; Alders, Robyn G.; Bagnol, B.; Msyoki, D.; Alonso, Silvia; Grace, Delia (2014)
Poultry is important for many poor smallholders, but infectious diseases, such as Newcastle disease, can drastically reduce the poultry population in a village and affects the food security and the livelihood of many farmers. Newcastle disease vaccination can reduce the spread of disease, but may be hard to access for smallholders if there is not a supportive system in place. In this paper, a district in Kenya is studied where there has been support for vaccination. It is shown that households in villages which had support were more likely to vaccinate, had more chickens and also know better the basic principle of a vaccine. The vaccinators themselves also reported that vaccination had improved the poultry keeping and the knowledge of the farmers. It is concluded that a supportive system is beneficial for increased vaccination.